Endoscopic Treatment of Ewing Sarcoma of the Sinonasal Tract. Issue 4 (June 2016) - Lepera, Davide; Volpi, Luca; Facco, Carla; Turri-Zanoni, Mario; Battaglia, Paolo; Bernasconi, Barbara; Piski, Zalán; Freguia, Stefania; Castelnuovo, Paolo; Bignami, Maurizio
Abstract : Abstract: The extra-skeletal form is an unusual type of Ewing sarcoma (ES) arising from soft tissue and in the literature there are reports of less than 50 patients describing the tumor in the paranasal sinuses and skull base. The histological diagnosis is crucial to plan the correct treatment and the molecular confirmation is mandatory in equivocal patients. A multimodality treatment with chemotherapy, surgery and radiotherapy improved the outcomes of these diseases during the last decades and a free-margin resection with the endoscopic transnasal technique is one of the most recent ways to manage these pathologies in selected patients, reducing the morbidities of the external approaches and preserving the quality of life of the patient. Here, the authors present the first patient of primary sinonasal ES free from disease after 5 years of follow-up and treated with an endoscopic endonasal approach and a second patient of sinonasal metastases of ES treated with and endoscopic transnasal approach.